EVOLUCIJA ILI EVOLUCIONIZAM, KREACIJA ILI KREACIONIZAM - Schneider, Robert; Smajić, Aid (Novi Muallim, 2004)
Ovo je prijevod dorađene verzije predavanja koje je, u okviru tribine Udruženja Ilmijje IZ-e u BiH «Ummet danas», na Fakultetu islamskih nauka u Sarajevu, 23.12.2004. godine, održao prof. dr. Robert J. Schneider. Dr. Schneider, iako umirovljeni profesor, još uvijek predaje na Odsjeku za filozofiju i religiju Apalachian State Univerziteta u SAD-u. Pored toga, on je kopredsjedavajući Odbora za nauku, tehnologiju i vjeru Episkopalne crkve u SAD-u. Zainteresirani neke od njegovih radova mogu naći na web-stranici “Science and Faith: perspectives on Christianity and science” (www.berea.edu/SpecialProject/scienceandfaith). Dr. Schneider, također, poziva sve čitaoce da svoje eventualne komentare na ovo predavanje i pitanja šalju na sljedeću e-mail adresu: rjschn39@bellsouth.net Priredio i s engleskog preveo: Aid Smajić Summary Some discussion over the relationship of the scientific theory of evolution to religious belief in creation has appeared in Bosnia and Herzegovina. To help clarify the issues, this article distinguishes the terminology of science from ideology and argues that when science and religion are understood for what each really is, and their boundaries are respected, they are not in conflict with one another. A brief summary of the modern scientific world picture of Big Bang cosmology and biotic evolution is followed by comments on challenges to this worldview by two forms of creationism found among American conservative, mostly Protestant, Christians: “young earth creationism” and “intelligent design.” The arguments of these groups are rejected by almost all scientists on scientific grounds, and by other Christians for theological reasons: both criticize creationism because it improperly crosses boundaries and mixes science and religion together. And, it subordinates scientific knowledge to religious ideology. The main portion of this article consists of a detailed description of the terminology of science and ideology. It explains the differences between “science” and “evolution” on the one hand, and the ideological belief systems of “scientism” and “evolutionism” on the other, and argues that “Darwinism” is not a correct term for the science of evolution. This exposition continues with an explanation of the difference between “creationism,” which is an ideology about origins, and “creation,” which is a theological concept about God’s relationship with the universe as God’s creation. Since theology answers the question “Who?” and science the question “How?” one does not have to choose between creation and evolution. They are not in conflict with each other, but can fit together in a religious understanding of the world.